(untitled) (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
This study investigates the empirical relationship between productive zakat and poverty alleviation in Indonesia using Autoregressive Distributed Lag (ARDL) approach over the period 1995-2023. The research employs comprehensive time series data from the National Zakat Board (BAZNAS) and Central Statistics Agency (BPS) to examine both short-run and long-run dynamics of zakat’s poverty reduction effectiveness. Augmented Dickey-Fuller tests confirm stationarity of all variables at I(0) level, while Bounds Test reveals strong cointegration relationship with F-statistic of 6.965159, significantly exceeding critical values at all significance levels. The findings demonstrate that productive zakat exhibits significant poverty reduction effects with long-run coefficient of -0.454382 (p=0.0559) and stronger short-run impact through first lag coefficient of -0.607590 (p=0.0180). Error Correction Model validates the adjustment mechanism toward long-run equilibrium, indicating zakat’s dual function as both sustainable redistributive instrument and short-term economic stabilizer. The model achieves exceptional explanatory power with R-squared of 98.97%, while CUSUM test confirms parameter stability across nearly three decades despite various economic shocks including the 1997-1998 Asian financial crisis. Results provide robust empirical evidence for integrating zakat into Indonesia’s national poverty alleviation strategy, demonstrating its effectiveness as both counter-cyclical policy tool and structural poverty reduction mechanism. The study contributes significantly to Islamic fiscal policy literature by quantifying zakat’s measurable economic impact through rigorous econometric methodology.